2015
DOI: 10.1108/bpmj-07-2014-0064
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing a decisive approach to manage quality costs through behavioural investigation

Abstract: Purpose -Nowadays companies in the world are selling products by keeping quality as a central value for the customer. Quality-related costs arise from a series of activities performed in order to maintain the quality of product or service. Like other activities of business, quality costs can be programmed, budgeted, measured and analysed to attain the objective of better quality at lower cost. The purpose of this paper is to formulate a decisive methodology to optimize total quality cost (TQC), comprehensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
1
20
1
3
Order By: Relevance
“…It can indicate the health of management performance in many areas of the organization. Measurements of quality-related costs also reveal shortcomings in cost allocation, standards, procedures, and practices which may remain undetected by the more commonly used production/operation and labour based analysis [9].…”
Section: B Discussionmentioning
confidence: 99%
“…It can indicate the health of management performance in many areas of the organization. Measurements of quality-related costs also reveal shortcomings in cost allocation, standards, procedures, and practices which may remain undetected by the more commonly used production/operation and labour based analysis [9].…”
Section: B Discussionmentioning
confidence: 99%
“…Likewise, Akenbor (2014) indicated that the quality cost is significant to customer satisfaction by eliminating internal and external failure costs for customers' satisfaction with health products. Consequently, the following two hypotheses are formulated: Moreover, Chopra and Singh (2015) asserted that much sufficient quality and productivity improvement tools generally find no place in small and medium-sized enterprises due to a lack of knowledge and resources. Whereas Starcevic et al (2015) confirmed the fact that as large companies have more resources than small and medium-sized companies, it is assumed that they will primarily quantify quality costs.…”
Section: This Is Whatmentioning
confidence: 99%
“…Quality has been long recognized as an important aspect in the decision-making of the consumers when a variety of products are available in the market. However, it is not only high quality which customers require, it is high quality with low price which attracts them and ultimately enable companies to outshine the competition (Chopra & Singh, 2015).…”
Section: Quality Costmentioning
confidence: 99%